An analysis of the impact of the Kimberly process certification scheme (KPCS) on national diamond regulattions regimes : the case of Zimbabwe - Gerber, Leonardus J. (University of Pretoria, 2017)
Mini Dissertation (LLM)--University of Pretoria, 2017.